An Administrative Claims Measure of Payments Made for Medicare Patients for a 30-Day Episode of Care for Acute Myocardial Infarction. Issue 6 (June 2015) - Kim, Nancy; Bernheim, Susannah M.; Ott, Lesli S.; Han, Lein; Spivack, Steven B.; Xu, Xiao; Volpe, Mark; Liu, Alex; Krumholz, Harlan M.
Abstract : Background: Understanding both cost and quality across institutions is a critical first step to illuminating the value of care purchased by Medicare. Under contract with the Centers for Medicare and Medicaid Services, we developed a method for profiling hospitals by 30-day episode-of-care costs (payments for Medicare beneficiaries) for acute myocardial infarction (AMI). Methods: We developed a hierarchical generalized linear regression model to calculate hospital risk-standardized payment (RSP) for a 30-day episode for AMI. Using 2008 Medicare claims, we identified hospitalizations for patients 65 years of age or older with a discharge diagnosis of ICD-9 codes 410.xx. We defined an AMI episode as the date of admission plus 30 days. To reflect clinical care, we omitted or averaged payment adjustments for geographic factors and policy initiatives. We risk-adjusted for clinical variables identified in the 12 months preceding and including the AMI hospitalization. Using combined 2008–2009 data, we assessed measure reliability using an intraclass correlation coefficient and calculated the final RSP. Results: The final model included 30 variables and resulted in predictive ratios (average predicted payment/average total payment) close to 1. The intraclass correlation coefficient score was 0.79. Across 2382 hospitals with ≥25 hospitalizations, the unadjusted mean payment was $20, 324 ranging from $11, 089 to $41, 897. The mean RSP was $21, 125 ranging from $13, 909 to $28, 979. Conclusions: This study introduces a claims-based measure of RSP for an AMI 30-day episode of care. The RSP varies among hospitals, with a 2-fold range in payments. When combined with quality measures, this payment measure will help profile high-value care. Abstract : Supplemental Digital Content is available in the text.